Purifikasi Kolagenase dari Usus Bandeng (Channos channos, Forskal) - Tatty Yuniarti; Tati Nurhayati; Agoes Mardiono Jacoeb (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Collagenase was purified from intestines of milkfish (Chanos chanos, Forskal) by extraction,ammonium precipitation, ion exchange chromatography on DEAE Sephadex A-50 and gelfiltration on a Sephadex G-100 column. The purification and yields were 114.731 fold and1.26% when compared to those in the starting-crude extract. The molecular mass of milkfishserine collagenase was estimated to be 14.63 kDa and 27.46 kDa.